2007
DOI: 10.1115/1.2768087
|View full text |Cite
|
Sign up to set email alerts
|

Soft Elastohydrodynamic Analysis of Radial Lip Seals With Deterministic Microasperities on the Shaft

Abstract: A numerical analysis is conducted to investigate the elastohydrodynamic effect of deterministic microasperities on the shaft of a lip seal. Various geometries of microasperities (triangular, square, hexagonal, and circular) are put into a 100×100μm2 unit cell and are investigated using Reynolds equation. For each shape, the area fraction of the microasperity is varied between 0.2 and 0.8, and the asperity height is varied between 0.3μm and 5μm. The calculation for load capacity and friction coefficient indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Nowadays, it is believed that both the seal and shaft roughness are important. Numerical models support this hypothesis, such as those by Gabelli and Poll [14], Shen and Salant [41], Hajjam and Bonneau [17]. Horve [22] has shown that a high seal roughness and a shaft roughness of 0.25-0.5 Ra are critical for long seal life and good sealing performance.…”
Section: Bearing Sealsmentioning
confidence: 89%
See 3 more Smart Citations
“…Nowadays, it is believed that both the seal and shaft roughness are important. Numerical models support this hypothesis, such as those by Gabelli and Poll [14], Shen and Salant [41], Hajjam and Bonneau [17]. Horve [22] has shown that a high seal roughness and a shaft roughness of 0.25-0.5 Ra are critical for long seal life and good sealing performance.…”
Section: Bearing Sealsmentioning
confidence: 89%
“…Horve [22] showed that high shaft surface roughness increases wear of the rubber lip. A shaft with engineered surface asperities, as suggested by Hadinata and Stephens [41], is extremely rough and may cause very high wear rates of the seal, especially when operating in the mixed lubrication regime during start/stop and low speeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the aspect of theory, Shinkarenko et al [7] obtained the pressure distribution in the fluid film and the elastic deformation of the elastomer by establishing and solving the theoretical model, which provided the best parameters for the design of the surface texture. Hadinata et al [8] conducted a numerical analysis to study the effect of deterministic microasperities on the elastohydrodynamic performance of lip seal. The micropores on the shaft surface show a significant decrease in friction and an increase in reverse pumping rate.…”
Section: Introductionmentioning
confidence: 99%